The influence of physique on dose conversion coefficients for idealised external photon exposures: a comparison of doses for Chinese male phantoms with 10th, 50th and 90th percentile anthropometric parameters. (22nd March 2017) - Lv, Wei; He, Hengda; Liu, Qian
Abstract: For evaluating radiation risk, the construction of anthropomorphic computational phantoms with a variety of physiques can help reduce the uncertainty that is due to anatomical variation. In our previous work, three deformable Chinese reference male phantoms with 10th, 50th and 90th percentile body mass indexes and body circumference physiques (DCRM-10, DCRM-50 and DCRM-90) were constructed to represent underweight, normal weight and overweight Chinese adult males, respectively. In the present study, the phantoms were updated by correcting the fat percentage to improve the precision of radiological dosimetry evaluations. The organ dose conversion coefficients for each phantom were calculated and compared for four idealized external photon exposures from 15 keV to 10 MeV, using the Monte Carlo method. The dosimetric results for the three deformable Chinese reference male phantom (DCRM) phantoms indicated that variations in physique can cause as much as a 20% difference in the organ dose conversion coefficients. When the photon energy was <50 keV, the discrepancy was greater. The irradiation geometry and organ position can also affect the difference in radiological dosimetry between individuals with different physiques. Hence, it is difficult to predict the conversion coefficients of the phantoms from the anthropometric parameters alone. Nevertheless, the complex organ conversion coefficients presented in this report will be helpful for evaluating the radiation risk for large groups of people with various physiques.